Anti‐apolipoprotein A‐1 autoantibodies as biomarker for atherosclerosis burden in patients with periodontitis. (11th October 2012) - Wick, P. A.; Mombelli, A.; Pagano, S.; Moren, X.; Giannopoulou, C.; Mach, F.; Roux‐Lombard, P.; Vuilleumier, N.
<x xml:space="preserve">Abstract</x> Background and Objective Anti‐apolipoprotein A‐1 (anti‐apoA‐1) IgG is a potential marker of atherosclerotic plaque vulnerability and cardiovascular complications. In patients with periodontitis the presence of anti‐apoA‐1 IgGs in serum and their association with atherosclerosis is unknown. Material and Methods One‐hundred and thirty subjects with periodontal disease and 46 healthy subjects, matched for age and gender, participated in this study. Anti‐apoA‐1 IgG, high‐sensitivity C‐reactive protein (hsCRP) and matrix metalloproteinase (MMP) ‐2, ‐3, ‐8 and ‐9 were measured in serum samples. An ankle‐brachial index (ABI) value below 1.11 served as a surrogate marker of atherosclerosis. Predictive accuracies of biomarkers for abnormal ABI were determined using receiver–operating characteristics curves and logistic regression analyses. Results Compared with healthy controls, periodontitis patients showed lower median ABI values (1.10 vs. 1.15; p < 0.0001), a higher prevalence of anti‐apoA‐1 IgG positivity (23.8% vs. 6.5%; p = 0.009) and higher concentrations of hsCRP (1.62 mg/L vs. 0.85 mg/L; p = 0.02) and MMP‐9 (435 μg/mL vs. 283 μg/mL; p < 0.0001). In patients younger than 50 years of age (n = 66), anti‐apoA‐1 IgG was found to be the best predictor for an abnormal ABI (area under the curve = 0.63; p = 0.03). Anti‐apoA‐1 IgG positivity increased the risk of having an abnormal ABI (odds ratio = 4.20; p = 0.04), independently of diabetes, smoking and body mass index. Conclusions Anti‐apoA‐1 IgG positivity and atherosclerosis, as reflected by abnormal ABI, were more prevalent in periodontitis patients than in age‐ and gender‐matched controls. In younger periodontitis patients, anti‐apoA‐1 IgG was found to be the best predictor of atherosclerosis burden.